2023
DOI: 10.1063/5.0142415
|View full text |Cite
|
Sign up to set email alerts
|

The role of boron related defects in limiting charge carrier lifetime in 4H–SiC epitaxial layers

Abstract: One of the main challenges in realizing 4H–SiC (silicon carbide)-based bipolar devices is the improvement of minority carrier lifetime in as-grown epitaxial layers. Although Z1/2 has been identified as the dominant carrier lifetime limiting defect, we report on B-related centers being another dominant source of recombination and acting as lifetime limiting defects in 4H–SiC epitaxial layers. Combining time-resolved photoluminescence (TRPL) measurement in near band edge emission and 530 nm, deep level transient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…27 The level labeled B-acceptor is associated to B Si and it is known to be a common impurity in 4H-SiC epilayers, originating from the graphite parts of chemical vapor deposition reactors. 3 On the other hand, the D-center was believed to be the B Si V C complex. 28,29 However, recent density functional theory calculations have revealed that the D-center can be identified as the B C .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…27 The level labeled B-acceptor is associated to B Si and it is known to be a common impurity in 4H-SiC epilayers, originating from the graphite parts of chemical vapor deposition reactors. 3 On the other hand, the D-center was believed to be the B Si V C complex. 28,29 However, recent density functional theory calculations have revealed that the D-center can be identified as the B C .…”
Section: Resultsmentioning
confidence: 99%
“…This, in turn, is affected by the presence of electrically active defects which behave as lifetime killers, like the carbon vacancy (V C ) and B-related defects. 2,3 The carbon vacancy (V C ) is a negative-U defect giving rise to two electrically active levels in the bandgap (E gap ) of n-type 4H-SiC, the Z 1=2 and the EH6/7 at 0.65 and 1.6 eV below the conduction band edge (E C ), respectively. 4 In particular, the Z 1=2 level is a recombination center affecting τ in bipolar devices.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…From the Arrhenius plots, the activation energies for hole emissions for B and D-center are estimated as E V + 0.21 and E V + 0.60 eV, respectively. They are well-known defects and have already been assigned to shallow boron (substitutional boron at the silicon site, B Si ) and deep boron (substitutional boron at the carbon site, B C ) [2,7,24,26,27].…”
Section: Resultsmentioning
confidence: 99%